DEVELOPMENT OF A STANDARDIZED POLYHERBAL CAPSULE TARGETING OXIDATIVE STRESS AND ARTHRITIS INFLAMMATION. - Khan Hajera N; Dr Noorul Hasan; Patil Rutuja; Faiza farooui; Shaikh sana Kausar (The Bioscan, 2025)
Purpose of the Work: The study aimed to develop a standardized polyherbal capsule combining Ochna obtusata, Tinospora cordifolia, and Boswellia serrata—three medicinal plants with known antioxidant, anti-inflammatory, and immunomodulatory properties—as a safer, multi-targeted herbal alternative for arthritis management. Methods: Individual plant extracts underwent preliminary phytochemical screening, quantitative estimation of total phenolic and flavonoid contents, and Fourier Transform Infrared Spectroscopy (FTIR) for chemical characterization. Three polyherbal fractions (PHF1–PHF3) were formulated in different ratios and optimized using Quality by Design (QbD) principles. The optimized capsule batches were then evaluated for physicochemical parameters, drug content uniformity, disintegration time, and in vitro release profile. FTIR was used to assess compatibility between extracts and excipients. Key Findings: Among all formulations, PHF2 showed the highest phenolic content (16.92 ± 0.057%) and flavonoid content (2.41 mg QE). The optimized capsule batch (S4) demonstrated excellent flow properties, uniform drug content (93.48 ± 0.4%), rapid disintegration (10.89 ± 0.1 min), and complete in vitro drug release (94.88% within 30 min). FTIR analysis confirmed chemical compatibility and stability of the formulation. Conclusion: The standardized polyherbal capsule was found to be pharmaceutically stable, compositionally consistent, and potentially effective in reducing oxidative stress–mediated arthritic inflammation. These findings suggest it could serve as a promising and safer herbal alternative to conventional arthritis therapies.